(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
History is laden with contentious issues and the history teacher has to negotiate how to handle such issues in almost every class. One of the propensities of both history teachers and learners is to make moral judgments over the historical issues that they engage with. Indeed, history is a subject that invariably carries the burden of civic education and nation-building and this can be done through identifying right from wrong. In this article, I present the thoughts of selected novice history teachers (who have been in service for at most 3 years) in relation to making moral judgments about the past in the classroom. The teachers identify the historical themes that they have considered making moral judgments about. They also explain the approaches that they have contemplated in this challenge. I then utilise Wineburg’s (2001) framework on moral ambiguity to explain the implications of the teachers’ views. I conclude that while South Africa’s history is flooded with moral references that make it almost impossible to avoid making judgments, the history teacher needs a usable framework that they can rely on for teaching all contentious issues.